Epidemiological profile of patients attended at the pain clinic at the Centro Universitário de João Pessoa – Unipê (Research, Society and Development, 2021)
This research was a descriptive and quantitative study, which aimed to evaluate the profile of patients seen at the Pain Clinic in a private institution. To this end, the objectives of characterizing patients regarding gender, age group and education level and verifying the prevalence of signs and symptoms of TMD and Orofacial Pain cases were met. The research was carried out at the Clínica Escola de Odontologia of Centro Universitário de João Pessoa - Unipê. The sample was conveniently obtained, consisting of 51 medical records. All necessary information was recorded in an online form for later statistical treatment of the data with the aid of descriptive statistical tools. 84.31% were female patients and 15.69% were male. The most recurrent age group was 30 to 40 years old, representing 31.37% of the participants, followed by 20 to 30 years old with 23.53%. Pain associated with another symptom constitutes 52.94% of the reasons why patients have sought care, 59% of patients were diagnosed with joint TMD and muscle TMD, 72% had sleep bruxism and while awake simultaneously, 92% diagnosed with disk displacement with reduction. The most affected muscles were the body of the superficial masseter (51%), followed by the anterior temporalis muscle (41.2%). It was concluded that women between 20 and 40 years old have sought the service with complaints of pain associated with other symptoms, with diagnoses of muscular and joint TMD and the association of the two types of bruxism being the most recurrent in the service.